Revaluation of Wrocław public use buildings in years 2005-2013 = Rewaloryzacja wrocławskich budynków użyteczności publicznej w latach 2005-2013 - Kirschke, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the years 2005-2013 in Wroclaw, there was commissioned to use hundreds of public buildings, including fifty revalued monuments These were: offices, museums, theatres, science and education facilities, as well as commercial buildings: banks, department stores, office buildings and hotels.
Keywords: obiekty użyteczności publicznej; budynki komercyjne; rewaloryzacja; Wrocław; buildings of public use; commercial buildings; restoration